PCV2 Cap protein nuclear import via importin α/β receptor: molecular insights and antiviral potential - Lin, Cui; Li, Na; Tao, Lihan; Li, Haiqin; Ma, Jiezhi; Wu, Chengcheng; Zhang, Fanfan; Fang, Shaopei; Tan, Jia; Huang, Yezhen; Zeng, Xiaofei; Zeng, Yanbing (Frontiers in Microbiology, 2025)
Porcine circovirus type 2 (PCV2) Cap protein serves as the primary structural component and plays multiple roles in viral infection. Previous studies have shown that Cap predominantly localizes to the nucleus, but the molecular mechanisms governing its nuclear import remain unclear. This study demonstrates that PCV2 Cap undergoes an active nuclear transport process dependent on Ran-GTP and importin α, but not transportin-1. Co-immunoprecipitation assays revealed interactions between Cap and several host nuclear transport receptors (NTRs), including all importin α subunits, importin 4, 5, 7, and 11. Furthermore, the small molecule inhibitor importazole (IPZ) partially inhibits the nuclear translocation of Cap and suppresses Cap expression, as well as PCV2 replication. While ivermectin (IVM) only impedes transport without affecting viral replication. These findings provide significant insights into the molecular mechanisms of PCV2-Cap nuclear import and highlight potential therapeutic targets for antiviral strategies aimed at disrupting viral capsid transport.